2019
DOI: 10.1002/psp4.12420
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Physiologically‐Based Pharmacokinetic Model for Tacrolimus in Living‐Donor Liver Transplantation: Perspectives Related to Liver Regeneration and the cytochrome P450 3A5 (CYP3A5) Genotype

Abstract: In adult patients after living‐donor liver transplantation, postoperative days and the cytochrome P450 3A5 (CYP3A5) genotype are known to affect tacrolimus pharmacokinetics. In this study, we constructed a physiologically‐based pharmacokinetic model adapted to the clinical data and evaluated the contribution of liver regeneration as well as hepatic and intestine CYP 3A5 genotypes on tacrolimus pharmacokinetics. As a result, liver function recovered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…A number of clinical studies evaluated the impact of intestinal CYP3A5 polymorphism (recipient CYP3A5 genotype) on tacrolimus pharmacokinetics. Several trials involving mainly living donor liver transplant recipients demonstrated important consequences of recipients' CYP3A5 genotype on tacrolimus concentration/dose ratios and on dose requirements in the first postoperative month, 21,22,24,25 whereas other studies emphasized the contribution of the donor (hepatic) CYP3A5 polymorphism to the variations in tacrolimus dose requirement over recipient (intestinal) CYP3A5 genotype 8–10 . Our findings confirmed an important role of CYP3A5 expression (the presence of CYP3A5*1 allele) of the liver graft in tacrolimus concentrations normalized by the dose and bodyweight; however, recipients' CYP3A5 genotype was failed to significantly modify dose‐adjusted tacrolimus trough levels.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…A number of clinical studies evaluated the impact of intestinal CYP3A5 polymorphism (recipient CYP3A5 genotype) on tacrolimus pharmacokinetics. Several trials involving mainly living donor liver transplant recipients demonstrated important consequences of recipients' CYP3A5 genotype on tacrolimus concentration/dose ratios and on dose requirements in the first postoperative month, 21,22,24,25 whereas other studies emphasized the contribution of the donor (hepatic) CYP3A5 polymorphism to the variations in tacrolimus dose requirement over recipient (intestinal) CYP3A5 genotype 8–10 . Our findings confirmed an important role of CYP3A5 expression (the presence of CYP3A5*1 allele) of the liver graft in tacrolimus concentrations normalized by the dose and bodyweight; however, recipients' CYP3A5 genotype was failed to significantly modify dose‐adjusted tacrolimus trough levels.…”
Section: Discussionsupporting
confidence: 76%
“…27 In the CYPtest group of the current study, the time for achieving target tacrolimus concentration was significantly reduced, confirming poten- A number of clinical studies evaluated the impact of intestinal CYP3A5 polymorphism (recipient CYP3A5 genotype) on tacrolimus pharmacokinetics. Several trials involving mainly living donor liver transplant recipients demonstrated important consequences of recipients' CYP3A5 genotype on tacrolimus concentration/dose ratios and on dose requirements in the first postoperative month, 21,22,24,25 whereas other studies emphasized the contribution of the donor to the control recipients on tacrolimus blood concentration guided dosing. Acute rejection has been demonstrated to be associated with low predose tacrolimus concentration (<10 ng mL −1 ) both in kidney and in liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations